INDUCTION OF AUTOPHAGY IN HUMAN CERVICAL CANCER CELL LINE (SIHA) BY CHAETOMORPHA LINUM (MULLER) KÜTZ. - Majumder, Indira; Paul, Subhabrata; Kundu, Rita (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
Objective: Algae is a rich source of various metabolites. Use of algae in traditional medicine was reported from very early days. The potential anticancerous activity of the algae was also reported by recent researches. In the present study, cell death mechanism induced by green alga Chaetomorpha linum (Muller)Â Kütz. was studied on human cervical cancer cell line, SiHa (Human papilloma virus-HPV 16+ve). Methods: Cells were treated with chloroform fraction of the Chaetomorpha linum (CLC). DNA fragmentation, cell proliferation, nuclear morphology, localization of autophagosomes and expression of relevant proteins were studied. Cell cycle and mitochondrial membrane potential (MMP) were assessed by fluorescence assisted cell sorting (FACS). Gas chromatography liquid spectrometry (GCMS) analysis of CLC was done to detect the algal compounds. Results: Preliminary experiments confirmed the absence of DNA fragmentation and altered nuclear morphology in the treated cells. In the Acridine Orange stained cells, the presence of autophagosomes was observed by both microscopy and FACS analysis. Decreased MMP was observed in the treated sets. Wound healing assay showed the inhibitory activity of CLC on SiHa cells. Increased expression of autophagic proteins, viz; LC3BII, p62/SQSTM, Beclin-1 and decreased expression of S6 were observed in the treated sets; indicating that autophagic cell death was induced. Preliminary qualitative chemical study and GCMS analysis detected the presence of saponins, glycosides, alkaloids, phenols, steroids and fatty acids in CLC. Conclusion: All these findings clearly suggested that the chloroform fraction of the algae was responsible for induction of apoptosis followed by autophagic cell death in SiHa and can serve as a potential candidate for anticancer drug development in future.